H∞ Fuzzy Control for Nonlinear Fourth-Order Parabolic Equation Subject to Input Delay - Kang, Wen; Ding, Da-Wei; Guo, Bao-Zhu; Li, Qing (IEEE transactions on systems, man, and cybernetics. Systems, 2022)
This article discusses H_{∞ } fuzzy control for the nonlinear fourth-order parabolic equation with input delay via collocated actuator/sensor pairs. We suggest that the interval [0, 1] is divided into M subdomains, where sensors provide spatially averaged/point discrete-time state measurements. The control design strategy is proposed based on output measurements. We derive constructive conditions ensuring that the resulting closed-loop system is internally exponentially stable and has H_{∞ } performance by means of the Lyapunov approach.